2016
DOI: 10.1007/s00445-016-1001-z
|View full text |Cite
|
Sign up to set email alerts
|

Recycled ejecta modulating Strombolian explosions

Abstract: Two main end-members of eruptive regimes are identified from analyses of high-speed videos collected at Stromboli volcano (Italy), based on vent conditions: one where the vent is completely clogged by debris, and a second where the vent is open, without any cover. By detailing the vent processes for each regime, we provide the first account of how the presence of a cover affects eruptive dynamics compared to open-vent explosions. For clogged vents, explosion dynamics are controlled by the amount and grain size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…As a conclusion, we suggest that the sideromelane and tachylite textures are inherited from a progressive subsurface cooling, inducing advanced degassing and secondary crystallization of the magma, which may occur either by (i) recycling material within active vents as already proposed for Etna (D'Oriano et al, 2014) and/or (ii) by directly cooling of the magma at its free surface facilitated by the slight decrease in the lava flux (Figures 2a and 2b, clogging of Vent B) as already observed on Stromboli (Gurioli et al, 2014) and/or (iii) by collapse of inner parts of the vent as we observed some collapse and instabilities features within the eruptive vents ( Figure 3) again observed at Stromboli (Capponi et al, 2016;Patrick et al, 2007). In each case, this degassed, crystallized, and viscous magma, represented by the sideromelane and mainly the tachylite component, formed a relatively impermeable magmatic layer at the fragmentation level within Vent B, during its decrease in activity mainly between 16 and 17 September.…”
Section: Sideromelane and Tachylite Scoria/ash Emission As The Indicasupporting
confidence: 83%
“…As a conclusion, we suggest that the sideromelane and tachylite textures are inherited from a progressive subsurface cooling, inducing advanced degassing and secondary crystallization of the magma, which may occur either by (i) recycling material within active vents as already proposed for Etna (D'Oriano et al, 2014) and/or (ii) by directly cooling of the magma at its free surface facilitated by the slight decrease in the lava flux (Figures 2a and 2b, clogging of Vent B) as already observed on Stromboli (Gurioli et al, 2014) and/or (iii) by collapse of inner parts of the vent as we observed some collapse and instabilities features within the eruptive vents ( Figure 3) again observed at Stromboli (Capponi et al, 2016;Patrick et al, 2007). In each case, this degassed, crystallized, and viscous magma, represented by the sideromelane and mainly the tachylite component, formed a relatively impermeable magmatic layer at the fragmentation level within Vent B, during its decrease in activity mainly between 16 and 17 September.…”
Section: Sideromelane and Tachylite Scoria/ash Emission As The Indicasupporting
confidence: 83%
“…A short acceleration exists but is not observed here due to geometrical constrains. Second and most relevant, almost all our explosions featured not one but multiple ejection pulses, also from more than one vent (Capponi et al, ; Gaudin et al, ; Scharff et al, ; Taddeucci et al, ). Our observations focus on the initial development of plumes in a region, which is relatively close to the vent area, and it remains open to discussion how much of the complexity we observe is preserved in the morphology of plumes at later moments and higher elevations above the vent.…”
Section: Discussionmentioning
confidence: 87%
“…A short acceleration exists but is not observed here due to geometrical constrains. Second and most relevant, almost all our explosions featured not one but multiple ejection pulses, also from more than one vent (Capponi et al, 2016;Gaudin et al, 2014;Scharff et al, 2015;Taddeucci et al, 2012). Our observations focus on the initial development of plumes Note.…”
Section: Diversity Of Plume Morphology and Evolutionmentioning
confidence: 83%
See 1 more Smart Citation
“…An extreme example comes from mild submarine eruptions observed at NW Rota-1 (Mariana arc), where eruption plumes are suppressed by the overlying water column9. Abundant pyroclast recycling has also been described at Stromboli volcano (Italy)11. In both cases, the extent of vent clogging affects the subsequent eruption intensity12 and grain size distribution9.…”
mentioning
confidence: 99%